2019
DOI: 10.1097/phm.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Compensation Strategies in Response to Fatiguing Propulsion in Wheelchair Users

Abstract: Objective The aims of the study were to examine whether fatigue-inducing wheelchair propulsion changes neuromuscular activation and propulsion biomechanics and to determine predictor variables for susceptibility to fatigue. Design This study with a quasi-experimental, one-group, pretest-posttest design investigates a population-based sample of wheelchair users with a spinal cord injury (n = 34, age: 50.8 ± 9.7 yrs, 82% males). Neuromuscular activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…This dichotomization has been used previously and was found to be capable of identifying persons who display more changes in neuromuscular activation associated to fatigue after the Figure-8 protocol in the same study population. 9 Tendon appearance-The region of interest (ROI) of each ultrasound image was defined from the interference pattern at the top of the images, created from the steel reference markers attached to the skin throughout the protocol (Figure 2). From the ROI, tendon characteristics including tendon width (mean distance between top and bottom border of the tendon), echogenicity ratio (mean pixel grayscale of tendon divided by mean pixel grayscale of muscle above tendon) and a co-occurrence matrix-derived measure contrast (intensity difference between a pixel and its neighbor in the vertical direction which is perpendicular to expected direction of the collagen fibers) were calculated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This dichotomization has been used previously and was found to be capable of identifying persons who display more changes in neuromuscular activation associated to fatigue after the Figure-8 protocol in the same study population. 9 Tendon appearance-The region of interest (ROI) of each ultrasound image was defined from the interference pattern at the top of the images, created from the steel reference markers attached to the skin throughout the protocol (Figure 2). From the ROI, tendon characteristics including tendon width (mean distance between top and bottom border of the tendon), echogenicity ratio (mean pixel grayscale of tendon divided by mean pixel grayscale of muscle above tendon) and a co-occurrence matrix-derived measure contrast (intensity difference between a pixel and its neighbor in the vertical direction which is perpendicular to expected direction of the collagen fibers) were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth detail on the recruitment and study procedures has been reported previously and is briefly described below. 9 This publication is part of a bigger project that aims to determine the effect of fatiguing wheelchair propulsion on risk factors for shoulder pain in persons with SCI. Compensation strategies in neuromuscular activation and propulsion biomechanics in response to fatiguing propulsion have been reported previously 9 , the current publication describes the ultrasound results which have not been presented elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations